Biocompatibility evaluation of sintered biomedical Ti-24Nb-4Zr-8Sn (Ti2448) alloy produced using spark plasma sintering (SPS) - Madonsela, Jerman S. (Vaal University of Technology, 2018)
Solid titanium (Ti), Ti-6Al-4V (wt.%), and Ti-24Nb-4Zr-8Sn (wt.%) materials were fabricated from powders using spark plasma sintering (SPS). The starting materials comprised of elemental powders of ASTM Grade 4 titanium (Ti), aluminium (Al), vanadium (V), niobium (Nb), zirconium (Zr), and tin (Sn). The powders were initially characterised and milled prior to sintering. The micronpowders were milled in an attempt to produce materials with nanostructured grains and as a result improved hardness and wear resistance. The produced solid Ti-24Nb-4Zr-8Sn alloy was compared to solid titanium (Ti) and Ti-6Al-4V (Ti64) on the basis of density, microstructure, hardness, corrosion, and biocompatibility. Relative densities above 99.0% were achieved for all three systems. CP-Ti and Ti64 had both 100% relative density, and Ti2448 showed a slightly lower density of 99.8%. Corrosion results showed that all three materials exhibited good corrosion resistance due to the formation of a protective passive film. In 0.9% NaCl Ti2448 had the highest current density (9.05 nA/cm2), implying that its corrosion resistance is relatively poor in comparison to Ti (6.41 nA/cm2) and Ti64 (5.43 nA/cm2), respectively. The same behavior was observed in Hank's solution. In cell culture medium, Ti2448 showed better corrosion resistance with the lowest current density of 2.96 nA/cm2 compared to 4.86 nA/cm2 and 5.62 nA/cm2 of Ti and Ti64 respectively. However, the current densities observed are quite low and insignificant that they lie within acceptable ranges for Ti2448 to be qualified as a biomaterial. Cell proliferation test was performed using murine osteoblastic cells, MC3T3-E1 at two cell densities; 400 and 4000 cells/mL for 7 days incubation. Pure titanium showed better cell attachment and proliferation under both conditions suggesting that the presence of other oxide layers influence cell proliferation. No significant difference in cell proliferation was observed between Ti64 and Ti2448.
M. Tech. (Department of Metallurgical Engineering, Faculty of Engineering Technology), Vaal University of Technology.
Keywords: Biocompatibility; Alloys; Titanium; Spark plasma sintering; Dissertations, Academic -- South Africa.; Biomedical materials.; Titanium alloys.; Sintering.